Determination of Suitable Hydrating Medium and Commercial Rice Variety for the Production of Dehydrated Quick-Cooking Rice. - Yong, Jennifer J.; De Leon, Sonia Y.
Three pre-hydrated media were used as pre-treatments of commercial rice for the production of dehydrated quick-cooking rice. These media were: A) distilled water (control), (B) 1% (1:1:) solution of calcium chloride and sodium citrate. and (C) 1% (1:1:1:) solution of calcium chloride, sodium citrate and calcium phosphate. Raw milled rice grains were hydrated at room temperature in each medium and were processed into dehydrated quick-cooking rice. Medium C proved to be the suitable hydrating Medium giving a product of well-separated grains that rehydrates in 5-6 minutes. The suitable hydrating medium (C) was applied to thhe pre-treatment of three commercial rice varieties, namely,IR-36, IR-60 and IR-64. Conditions needed to dehydrate, gelatinize, dehydrate and rehydrate each processed variety were established. Upon evaluation, processed IR-60 treated with 1% (1:1:1:) calcium chloride, sodium citrate and calcium phosphate was found to be the most acceptable quick-cooking product among the three varieties. This grayish-white, moderately separated product gave the highest yield (0.94) in terms of weight, highest bulk density (0.43) and least rehydration of 5 minutes in boiling water. Comparison of rehydrated quick-cooking IR 60 against a conventionally cooked one of the same variety revealed no significant difference in over-all sensory attributes
Thesis (B.S.F.T.)--University of the Philippines, Diliman.
Typescript.
Keywords: rice varieties